2007
DOI: 10.1108/13665620710735611
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for undergraduates doing practitioner investigations at work

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…Production in or for the workplace has been recognised as a part of final project evidence in work based learning (Brennan and Little, 1996;Costley and Armsby, 2007). However, the professional artefact was conceived of to recognise the potential limits of a written report in representing a "portfolio of work based 'products' with evaluative commentary drawing out what was learned" (Brennan and Little, 1996, p. 78).…”
Section: Rationale For the Professional Artefactmentioning
confidence: 99%
See 1 more Smart Citation
“…Production in or for the workplace has been recognised as a part of final project evidence in work based learning (Brennan and Little, 1996;Costley and Armsby, 2007). However, the professional artefact was conceived of to recognise the potential limits of a written report in representing a "portfolio of work based 'products' with evaluative commentary drawing out what was learned" (Brennan and Little, 1996, p. 78).…”
Section: Rationale For the Professional Artefactmentioning
confidence: 99%
“…The BAPP (Arts) curriculum uses a foundation of transdisciplinary practice (Gibbons et al, 1994;Costley and Armsby, 2007) that seeks to connect academic study to situated knowledge in settings beyond the university. As work based students co-produce and integrate various forms of knowledge in the workplace, the notion of the professional artefact offers an apposite way to communicate learning within the work environment.…”
Section: Introductionmentioning
confidence: 99%
“…Activities may be small and localised, forming the basis for a single module in an undergraduate programme, or they can be major undertakings that produce significant organisational or professional change and lead to the award of a doctorate. The majority of work-based projects can be conceptualised as research and involve learners in becoming practitioner-researchers (Costley & Armsby 2007b), even if to the learner it is the practice element -the desire to create (and learn from) change -that is in the foreground, with the research in the background (Doncaster & Lester 2002, Boud & Tennant 2006.…”
Section: Work-based Learning As University Practicementioning
confidence: 99%
“…Given Boud and Solomon's (2001) desire to develop transdisciplinary research approaches to work-based studies, the results seem disappointing. Costley and Armsby (2007) failed to find sufficient evidence in their limited study of undergraduate work-based study students. Workman (2007) identified a lack of appreciation of structure in her study of (insider workplace) researchers and suggested an approach not dissimilar to that advocated here.…”
Section: Professionals' Application Of Transidisciplinary Practicementioning
confidence: 89%